Circulating MicroRNAs Identified in a Genome-Wide Serum MicroRNA Expression Analysis as Noninvasive Biomarkers for Endometriosis - Wang, Wen-Tao; Zhao, Ya-Nan; Han, Bo-Wei; Hong, Shun-Jia; Chen, Yue-Qin (The journal of clinical endocrinology and metabolism, 2013)
Context:There is currently no reliable noninvasive biomarker for the clinical diagnosis of endometriosis. Previous analyses have reported that circulating microRNAs (miRNAs) can serve as biomarkers for a number of diseases.Objective:The study aims to detect the serum miRNAs that are differentially expressed between endometriosis patients and negative controls to evaluate the potential of these miRNAs as diagnostic markers for endometriosis.Design:A total of 765 serum miRNAs were profiled using a TaqMan microRNA array in a pool of 10 endometriosis patients and a pool of 10 negative controls, and a set of selected miRNAs were further analyzed in a validation cohort consisting of sera from 60 patients and 25 controls including 10 samples used in array profiling.Results:The relative expression levels of miR-199a and miR-122 were found to be up-regulated in endometriosis patient samples compared with control samples, whereas miR-145*, miR-141*, miR-542-3p, and miR-9* were down-regulated in endometriosis patients. Importantly, the relative expression of miR-199a (P < 0.05) and miR-122 can be used to discriminate between severe and mild endometriosis. We also found that miR-199a is well correlated with pelvic adhesion and lesion distribution (P < 0.05) and associated with hormone-mediated signaling pathways. Furthermore, we investigated the diagnostic value of these molecules and confirmed the optimal combination of miR-199a, miR-122, miR-145*, and miR-542-3p with area under the curve of 0.994 (95% confidence interval = 0.984–1.000, P < 0.001) and a cutoff point (0.4950) of 93.22% sensitivity and 96.00% specificity.Conclusions:Our study demonstrated that the circulating miRNAs miR-199a, miR-122, miR-145*, and miR-542-3p could potentially serve as noninvasive biomarkers for endometriosis. miR-199a may also play an important role in the progression of the disease. This is the first report that circulating miRNAs serve as biomarkers of endometriosis.